Transconjunctival approach to peribulbar block - McGrath LA (Dove Medical Press, 2013)
Lindsay A McGrath,1,2 Christopher Bradshaw3,4 1University of Queensland, School of Medicine, Brisbane, Qld, Australia; 2City Eye Centre, Brisbane, Qld, Australia; 3Royal Brisbane and Women’s Hospital, Department of Anesthetics, Brisbane, Qld, Australia; 4Queensland Eye Hospital, Brisbane, Qld, Australia Abstract: As increasing numbers of anesthetists perform eye block anesthesia, thorough understandings of peribulbar injection techniques are important for safe practice. There is uncertainty in the literature regarding the optimum needle length, entry point, volume of injectate, and use of single vs double-injection techniques. A modified technique of peribulbar block anesthesia is presented, which offers increased safety, simplicity, low cost, and little change to instrumentation. Keywords: injection, ropivacaine, anesthesia